2011
DOI: 10.1007/s00464-011-1636-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of standard versus laparoendoscopic single-site surgery (LESS) totally extraperitoneal (TEP) inguinal hernia repair

Abstract: Our short-term experience with LESS TEP inguinal hernia repair has shown that in experienced hands, inguinal hernia repair via the LESS TEP technique is as safe as the standard TEP technique. However, based on our evidence, we currently believe that the LESS TEP technique is not an efficacious surgical alternative to the standard TEP technique for inguinal hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 17 publications
2
90
2
Order By: Relevance
“…Some reports showed comparable postoperative pain, and other reports didn't mention about pain between two groups. 1,5,6,10 In our study and some other researchers described that patients suffered more pain on immediate postoperative day. 1,3 In our SUTI-TEP experience of using many different kinds of SILS port including home-made glove port, it seemed that patients suffered more immediate postoperative pain after SILS than after conventional multi-port surgery (data not shown).…”
Section: Discussionsupporting
confidence: 68%
“…Some reports showed comparable postoperative pain, and other reports didn't mention about pain between two groups. 1,5,6,10 In our study and some other researchers described that patients suffered more pain on immediate postoperative day. 1,3 In our SUTI-TEP experience of using many different kinds of SILS port including home-made glove port, it seemed that patients suffered more immediate postoperative pain after SILS than after conventional multi-port surgery (data not shown).…”
Section: Discussionsupporting
confidence: 68%
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…One study commented on a previous report. 37 Three studies 22,40,45 compared LESS TEP with LAP TEP and were combined to produce a summative outcome. A flow chart of the literature search according to PRISMA guidelines 48 is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Further developments, especially in relation to cosmesis, include single-port surgery but may take longer to perform than standard TEP repairs. 36 Azurin et al 22 Srinivasan et al 25,a Paajanen et al 24 Kluin et al Because of the spectrum of challenges involved when treating sports hernias, it is important to ensure that a specific patient-centered, multidisciplinary approach is used, 10,37 and that may involve tenotomy for adductor type pain. 14,24,26 Furthermore, should a TEP repair be performed prophylactically in patients with asymptomatic contralateral groins?…”
Section: Discussionmentioning
confidence: 99%